Sport Human Connection as a marketing management application for sports service providers - Adi, Sapto; Fathoni, Abi Fajar; Hwa, Michael Chia Yong (SPORT TK-EuroAmerican Journal of Sport Sciences, 2025)
The management of the Indonesian sports industry provides no room for sport service providers to publicize their services. Consequently, Indonesian society is left with limited options in sport services, such as coaches, sport schools, masseurs, physiotherapists, and so forth. This research and development established a Sport Human Connection (SHC), an online smartphone software that facilitates the marketing and publication of sports services. The smartphone developed software is used extensively to promote services for sport. However, the online software required some adjustment so that the management of sport services can be better facilitated. In this study, a product was developed as a solution to the existing problems. The developed product was tried out on 60 sports actors (SA). The data were gathered using a questionnaire with open-ended and close-ended questions about the developed product. The SHC system carries various benefits for sports services, including service publication and promotion, along with the exhibition of the profession's legality and achievement. Besides, the system also facilitates communication between the service provider and society, along with the communication among sport service providers. The study suggest that the SHC has facilitated the sport service providers by helping them promote their services. Further, the SHC system should be promoted to sports service providers and to society.